Comparison of virtual private network (VPN) using mobile internet protocol (MIP) and internet protocol (IP) / Norhacida Abdullah - Abdullah, Norhacida (2006)
This paper presents a comparison of Virtual Private Network (VPN) using Mobile IP (MIP) and Internet Protocol (IP). Advancements in virtual private networking technologies allowed the easy use of public shared wireline infrastructures such as the Internet to securely transmit private data traffic, thus extending the reach of private netWorks by allowing remote users to connect to remote resources, information and services. This project is to compare and evaluate the performance of Virtual Private Network using Mobile IP (MIP) and IP. Study how IPSec being operate in VPN in conjunction with wireless access. This security services offered includes access control, connectionless integrity, and data origin authentication, protection against replays, confidentiality and limited traffic flow confidentiality. In conclusion, this project is proposes an analysis the performance of Virtual Private Network (VPN) using Mobile IP and fixed IP. This performance will be analyzed using OPNET simulation software.